The effects of cisplatin on developing nociceptive pathways - Lloyd, Joseph (2017)
Survivability of paediatric cancers has tripled since the 1970s, however treatment comes with severe side effects. Cisplatin is the main treatment for solid state tumours, the most common form of paediatric cancers. Cisplatin’s main dose-limiting factor is Chemotherapy Induced Peripheral Neuropathy (CIPN), a chronic pain disorder that can persist for decades beyond the end of treatment, severely affecting quality of life. This can be especially damaging in children, where early life insults can fundamentally alter the development of spinal nociceptive pathways. This study aimed to determine the extent of glial and neuronal changes in developing spinal nociceptive pathways following chemotherapeutic early life insult. Sprague Dawley rat pups were given 1mg/kg cisplatin (cis) (0.5mg/ml) or vehicle (veh) via intraperitoneal (IP) injections for 5 days from postnatal day 7 to 11. At a juvenile (P13) and adult (P45) time-point, animals were given IP injection of pentobarbital and fixed via perfusion of 4% paraformaldehyde. Blood, DRGs and spinal cords were removed and stored in 30% sucrose in PBS plus 0.05% sodium azide. Immunohistochemistry performed on 40µm sections of the spinal cord lumbar enlargement. Antibodies for neuronal and glial targets involved in nociceptive pathways used were: neurones (NeuN), Microglia (IBA1), astrocytes (GFAP), Aβ fibres (NF200), non-peptidergic neurones (IB4), peptidergic neurones (CGRP), nerve growth factor receptors (TrkA) and interneurones (vGLUT2). The dorsal horn (DH) was imaged on confocal microscope and regions of interest (ROI) in laminae I-V analysed using ImageJ and Graphpad Prism. A statistically significant (p=0.0039) increase in IL6 was shown in the blood plasma of the cisplatin animals (131.9±31.91 pg/ml) compared to the vehicle animals (38.00±6.748 pg/ml). There were no significant differences between cisplatin and vehicle animals in dorsal horn neurones or astrocytes at either time point. Microglia cell counts in the dorsal horn were significantly decreased at the juvenile time point in the Cisplatin treatment group. Cisplatin induced significant increases in dorsal horn expression of Aβ-fibre and non-peptidergic C-fibre terminations at both time-points, in the Cisplatin treatment group. TrkA expression in dorsal horn peptidetgic C-fibre terminations was increased at both time-points, however, CGRP expression was only initially increased at the juvenile time-point but showed no difference to the veh at the adult time-point. Interneuron expression was increased at both time-points. This study has shown that paediatric Cisplatin treatment causes significant chronic changes in PNS and CNS nociceptive histology, potentially underlying the chronic pain behaviours that Cisplatin has previously been shown to produce. Further research is required to fully establish the link between changes in cellular histology and animal behaviour and to understand the full extent of Cisplatin’s effect on the CNS.